2009
DOI: 10.1037/a0014224
|View full text |Cite
|
Sign up to set email alerts
|

Compared with what? The effects of different comparisons on conceptual knowledge and procedural flexibility for equation solving.

Abstract: Researchers in both cognitive science and mathematics education emphasize the importance of comparison for learning and transfer. However, surprisingly little is known about the advantages and disadvantages of what types of things are being compared. In this experimental study, 162 seventh-and eighth-grade students learned to solve equations (a) by comparing equivalent problems solved with the same solution method, (b) by comparing different problem types solved with the same solution method, or (c) by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(138 citation statements)
references
References 57 publications
(166 reference statements)
7
128
0
3
Order By: Relevance
“…The current study uses a method previously employed in a different domain [13] to identify groups of students in a math ITS that differ in how they apply strategies to solving equations. First, our findings from the behavioral pre-test replicated results from RittleJohnson and Star [1,7], showing a correlation between strategic flexibility and procedural knowledge. Understanding how strategic flexibility is represented during tutoring is less clear.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The current study uses a method previously employed in a different domain [13] to identify groups of students in a math ITS that differ in how they apply strategies to solving equations. First, our findings from the behavioral pre-test replicated results from RittleJohnson and Star [1,7], showing a correlation between strategic flexibility and procedural knowledge. Understanding how strategic flexibility is represented during tutoring is less clear.…”
Section: Discussionsupporting
confidence: 79%
“…In the current study, we use Hidden Markov Modeling (HMM) to cluster participants into strategically distinct groups. We present evidence supporting the hypothesis that these groups differ on a measure of strategic flexibility collected using the pencil and paper test developed by Rittle-Johnson and Star [7]. Furthermore, we use this HMM method to explore how flexibility presents itself in a math ITS as differences in tutor behavior.…”
Section: The Current Studymentioning
confidence: 55%
See 2 more Smart Citations
“…Gick and Hoyoak found that the best transfer was achieved by instruction that asked students to compare two examples (or analogs) of a general solution schema in the context of a symbolic abstraction (a diagram) representing the general solution schema. Other studies have also demonstrated the eff ectiveness of prompting for example comparisons (Gentner et al, 2009;Rittle-Johnson & Star, 2009), or for providing an abstraction of a general rule, pattern, or theory behind solutions (e.g., Judd, 1908;Holland, Holyoak, Nisbett, & agard, 1986). How might we best map laboratory results like these onto educational practice?…”
Section: Finding the Right Level Of Generality To Apply An Instructiomentioning
confidence: 99%